2007
DOI: 10.1002/bmc.936
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an immunoaffinity extraction column for enrichment of adducts between human serum albumin and hexahydrophthalic anhydride in plasma

Abstract: An immunoaffinity extraction (IAE) column was prepared for extraction of adducts between human serum albumin (HSA) and hexahydrophthalic anhydride (HHPA). HHPA is a strong sensitizer inducing immunoglobulin E antibodies in vivo. Polyclonal antibodies from a rabbit immunized with keyhole limpet hemocyananin-HHPA conjugate were purified using a Protein A Sepharose gel. To obtain antibodies with optimal affinity towards HHPA-protein adducts, HHPA-specific antibodies were selected using an N-hydroxysuccinimide-Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In such instances, the matrix effects may interfere in the analysis, and a sample purification step would be necessary. Johannesson et al (27) have shown that HHPA-adducted human serum albumin can be purified with immunoaffinity chromatography from plasma. This could be applied to the PA adducts as well, but for this procedure, more work has to be performed to obtain a final biological monitoring method.…”
Section: Discussionmentioning
confidence: 99%
“…In such instances, the matrix effects may interfere in the analysis, and a sample purification step would be necessary. Johannesson et al (27) have shown that HHPA-adducted human serum albumin can be purified with immunoaffinity chromatography from plasma. This could be applied to the PA adducts as well, but for this procedure, more work has to be performed to obtain a final biological monitoring method.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hb from exposed workers should be analyzed to determine the levels of adducts in these subjects. If the adduct levels are found to be too low to be detected, there are ways to solve this problem; e.g., Georgieva et al [31] and Johannesson et al [32] have shown that adducted peptide can be purified using immunoaffinity chromatography. It is also possible worth evaluating if peptides from human serum albumin or other high abundant plasma proteins can be analyzed.…”
Section: Biomarkers Of Exposurementioning
confidence: 98%